The Implementation of Moral Education Values in the Book of Morals Lil Banin Juz 1 in Forming the Students at Nurul Anwar Islamic Boarding School - Fidayanti, Alfina; Aziz Q, Ikhwan; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia which play a role in shaping the character of students through moral education. However, there are still students who do not understand ethics, such as a lack of respect for their elders, being late for class, and a lack of attention to learning. One of the books used in moral education in Islamic boarding schools is Akhlak Lil Banin Juz 1, which contains moral values to shape the character of good students. Therefore, this research aims to determine the implementation of moral education values in the book Akhlak Lil Banin Juz 1 in the character formation of grade 3 students at the Nurul Anwar Islamic Boarding School, Metro City. There are still some students who do not understand morals, lack student ethics towards older people in their behavior, are late for class, sleep during the learning process, do not pay attention to the teacher's explanations so that when asked directly by the teacher the students are confused about the answer. The author used qualitative research methods in this research. Researchers chose to use field research, where data collection is carried out directly in the field by observing phenomena in natural conditions. The results of this research are that the implementation of moral education must be carried out from an early age because it is very important for social life in society or in the environment. The best application of akhlakul karimah is to get used to living in a religious environment such as in an Islamic boarding school or ma'had which is based on strong religious education, thereby prioritizing good habits, such as the saying "You can because you get used to it".